Conformational studies of Ant–Pro motif-incorporated cyclic peptides: gramicidin S and avellanin. (20th December 2017) - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J.
Abstract : Conformational studies suggest that an Ant D Pro motif-incorporated synthetic gramicidin S analog retains β-sheet conformation, while its truncated analog avellanin disturbs the β-sheet conformation. Abstract : This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo -β (C9) Ant– D Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a β-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the β-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.